Web-based application that support active learning - Mantikayan, Jonathan Mamangkiang; Ayu, Media Anugerah (IIUM Press, 2011)

(untitled)
The major use of web-based instruction is to enhance traditional, on-campus courses, where the benefit ofWeb enhancement as a supplemental resource is less obvious. The competition fostered in today's environment is demanding increased accountability of idealistic teachers and re-evaluation of traditional teaching methods. Without reliable and valid instructional measurement systems, it is virtually impossible to benchmark new techniques. Web based application can be able to support active learning. This study describes different web based application tools that can be utilized to support active learning in the classroom